Effect of Dietary Supplementation of Lauric Acid on Performance and Carcass Characteristics in Commercial Broiler Chicken - Bhalsing, Jivan; D. Nagalakshmi; M. Venkateshwarlu; S.V. Rama Rao (Indian Journal of Animal Nutrition, 2026)
An experiment was conducted to evaluate the effect of dietary lauric acid supplementation as alternative to antibiotic growth promoter (AGP) at graded levels on performance and carcass traits in commercial broilers. Three-hundred-day-old commercial broiler chicks were randomly allotted to 6 dietary treatments with 10 replicates of 5 chicks in each. Corn soyabean meal based basal diet (BD) was formulated for pre-starter (1-2 weeks), starter (3-4 weeks) and finisher (5-6 weeks) phases without antibiotic growth promoter (negative control). Positive control diet was the BD having 0.035% chlortetracycline as AGP. Remaining four experimental diets were formulated by supplementing lauric acid to BD at rate of 0.05% (LA-50), 0.075% (LA-75), 0.1% (LA-100) and 0.2% (LA-200), respectively. Body weights, feed intake and feed conversion ratio (FCR) were measured at weekly intervals. At the end of 6th week, one bird from each replicate was selected randomly for studying carcass characteristics. Overall body weight gain (BWG) was higher (P